An exploration of gamification as a teaching method for entrepreneurship education amongst black youth entrepreneurs in townships and periurban areas - Mkuzo, Anele (Graduate School of Business (GSB), 2024)
Due to the increase in youth unemployment, one of the suggestions has been a move to encourage young people to pursue entrepreneurship. But entrepreneurship requires certain skills and knowledge that some individuals might not possess. This sequential embedded mixed method research investigated the purposeful sampling of entrepreneurs, ED practitioners and serious game founders and developers, in an effort to discover whether gamification can be used as a teaching method for entrepreneurship education amongst black youth in the township and peri-urban areas. This was done through qualitative methods, which were individual interviews and focused groups and quantitative method, which was in the form of a serious game prototype. The primary question was whether gamification could become a teaching method for entrepreneurship education among black youth entrepreneurs in townships and peri-urban areas. The three secondary questions were: • How do ED programmes address youth unemployment? And what are the expectations of these programmes? • How do youth entrepreneurs in the township and peri-urban areas find and learn new information? • What does gamification data reveal about learning and development for youth entrepreneurs in the township and peri-urban areas? The research findings from the study were that the pre-gamification phase revealed the lack of skills and experience, inadequate big-picture thinking and achievement mindset, lack of openness to be taught, new entrants' issues into the space, and being stretched beyond the comfort zone were some of the factors that are contributing towards the challenges that are faced by the youth entrepreneur. This implies that any intervention, such as the focus of this study, which is gamification, should be looked at through the lenses of these challenges and needs of the young entrepreneurs. What was also evident from the findings was that the young entrepreneurs had expectations of inclusive and continual development, skills development and mentorship but at the same time had business-specific expectations such as assistance with access to funding, market access, networking with their peers and industry players, despite the fact that several gaps were highlighted in the ED programme by both the young entrepreneurs and ED practitioners. These were unintended disempowerment, lack of followthrough and incompleteness, inadequate breakthrough with new solutions and multiple ineffective ED programmes. These entrepreneurs indicated that they learn by experience, use internet searches and online learning, and prefer creative and fun learning as well as group learning with family, which are good attributes for gamification as a learning tool. The findings for the second research question indicated that there were multiple groups; some only had theoretical knowledge of gaming, though they did not have practical knowledge. They were more positive towards their use as a learning tool than were other groups of entrepreneurs who had experience in gamification as well as ED practitioners. Some were still using the game for recreation, but it helps to de-stress and refocus, and for others, it helps to improve their propensity to use the technology. Despite recreation, de-stress, refocus and improving technology use behaviour are not the core of gamification; these are critical for building a young entrepreneur for success. The findings for the third question revealed that the gamification results were inconclusive on whether the application was an effective learning vehicle in this instance, given the average outcomes of quizzes. Although the quizzes produced middling results, these materials were still interesting for all audiences. Despite this, the post-gamification interviews based on their experience confirm that gamification has become a teaching method for black youth entrepreneurs in townships and peri-urban areas